PENDAMPINGAN BIMBINGAN TEKNIS PENYELESAIAN TUGAS AKHIR MAHASISWA IAIN PALANGKA RAYADI MASA TRANSISI WABAH COVID-19 - Noor Hujjatusnaini (Adiba Aisha Amira, 2022)
Completion of the final project on time is an important aspect that must be planned more programmed during education. Students of the Biology Tadris Study Program IAIN Palangkaraya FY 2021/2022 have delays in finding ideas and ideas in completing their final project during the transition period of the Covid-19 outbreak, where 93% of students stated that they still did not have clear ideas and ideas, 7% of the students stated that he was still in the stage of trying to express ideas in the form of a draft proposal. The technical guidance assistance program for the completion of the final project is one of the Mentoring Programs initiated by the Biology Tadris Study Program, which in its implementation can be used as one of the lecturers' independent services. The program implementation aims to assist in achieving the target of completing student final assignments on time after the pandemic. The mentoring and evaluation of the success of the mentoring program was carried out from January to April 2022. Based on the evaluation results that the implementation of the mentoring program there were very significant results, where the delay in student ideas and ideas (93%) experienced completeness (100%) at the end of the week 4 mentoring, where 10% of students have drafted proposals and are able to develop research instruments, 73% have been in the data mining stage in the field, and 17% have succeeded in the data analysis stage. The findings in this case study are in the form of mentoring program achievements that must be published, in the hope that they can be used as further references.